2015
DOI: 10.5194/bg-12-4711-2015
|View full text |Cite
|
Sign up to set email alerts
|

N<sub>2</sub>O fluxes from the littoral zone of a Chinese reservoir

Abstract: Abstract. There have been few studies of greenhouse gas emissions from reservoirs, despite the remarkable growth in the number of reservoirs in developing countries. We report a case study that focuses on the littoral zone of a major Chinese reservoir, where we established measurements of N2O fluxes using the static chamber technique at five different water levels (deep water, shallow water, seasonally flooded, control for seasonally flooded, and non-flooded). The "control for seasonal flooded" had similar veg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…There may be other sources of error, for example the linear models (Table 3) used in evaluating the balance were themselves rather weak, especially the N 2 O model. However, the N 2 O emission (6.8 µg m −2 h −1 on average, see [17]) was small compared to that of CO 2 and CH 4 (1.3 mg m −2 h −1 on average, see [18]), and so we would not expect any big influence on the overall balance from the lack-of-fit of the N 2 O model. Finally, for the flooded areas, the flux observed after removal of shoots might include respiration of the phytoplankton.…”
Section: Comparison With Other Greenhouse Gases and The Source/sink Qmentioning
confidence: 91%
See 4 more Smart Citations
“…There may be other sources of error, for example the linear models (Table 3) used in evaluating the balance were themselves rather weak, especially the N 2 O model. However, the N 2 O emission (6.8 µg m −2 h −1 on average, see [17]) was small compared to that of CO 2 and CH 4 (1.3 mg m −2 h −1 on average, see [18]), and so we would not expect any big influence on the overall balance from the lack-of-fit of the N 2 O model. Finally, for the flooded areas, the flux observed after removal of shoots might include respiration of the phytoplankton.…”
Section: Comparison With Other Greenhouse Gases and The Source/sink Qmentioning
confidence: 91%
“…Elsewhere, we have reported the emissions of CH 4 and N 2 O from the Miyun Reservoir, and we demonstrated that this littoral zone can be regarded as a hot spot for emissions [17,18]. In the present paper, we evaluate (i) the spatiotemporal variation of CO 2 emissions from the littoral zone; and (ii) the influence of environmental factors, especially flooding.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations